(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article discusses the dialectic of the formation of the principles of ownership among young people and the optimal possibilities and specific features of its strengthening. The socio-economic reforms implemented in Uzbekistan regarding the formation of the principles of ownership among young people are discussed.